2021
DOI: 10.3390/chemistry3030069
|View full text |Cite
|
Sign up to set email alerts
|

Questions in the Chemical Enzymology of MAO

Abstract: We have structure, a wealth of kinetic data, thousands of chemical ligands and clinical information for the effects of a range of drugs on monoamine oxidase activity in vivo. We have comparative information from various species and mutations on kinetics and effects of inhibition. Nevertheless, there are what seem like simple questions still to be answered. This article presents a brief summary of existing experimental evidence the background and poses questions that remain intriguing for chemists and biochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 166 publications
(204 reference statements)
1
2
0
Order By: Relevance
“…Significantly down-regulated MAO gene expression, protein levels and activity are in line with recent work suggesting that MAO activity stimulates mitochondrial respiration to support the bio-energetic demands of phasic dopamine release (Graves et al, 2020). Interestingly, calcium regulates the anchoring of MAOs at the mitochondrial surface, promoting the catalytic activity of MAO-A but not MAO-B (Ramsay and Albreht, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…Significantly down-regulated MAO gene expression, protein levels and activity are in line with recent work suggesting that MAO activity stimulates mitochondrial respiration to support the bio-energetic demands of phasic dopamine release (Graves et al, 2020). Interestingly, calcium regulates the anchoring of MAOs at the mitochondrial surface, promoting the catalytic activity of MAO-A but not MAO-B (Ramsay and Albreht, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…Research has shown that the expression of MAO-B increased with age, and activity of MAO-B could increase neuronal damage [ 24 ]. Several research teams have investigated the synthesis, biological assessment, and computational aspects of cholinesterase and MAO inhibitors [ 25 , 26 , 27 , 28 ]. Potential MAO-B inhibitors could also be screened from natural products of roots of Platycodon grandiflorus (Jacq.)…”
Section: Introductionmentioning
confidence: 99%
“…This compound is then metabolized by monoamine oxidase B (MAO-B) forming N-methylimidazole acetaldehyde [10]. MAO-B is a promiscuous enzyme that acts on many different biogenic amines, such as dopamine, serotonin, phenylethylamine, benzylamine, epinephrine, and norepinephrine [11,12]. On the other hand, MAO-B distinguishes between two similar compounds, histamine and its methylated form, N-methylhistamine, showing both in vivo and in vitro selective activity towards the latter compound [13][14][15].…”
Section: Introductionmentioning
confidence: 99%